2015
DOI: 10.3892/ijo.2015.2974
|View full text |Cite
|
Sign up to set email alerts
|

Crucial roles of thymidine kinase 1 and deoxyUTPase in incorporating the antineoplastic nucleosides trifluridine and 2′-deoxy-5-fluorouridine into DNA

Abstract: Trifluridine (FTD) and 2′-deoxy-5-fluorouridine (FdUrd), a derivative of 5-fluorouracil (5-FU), are antitumor agents that inhibit thymidylate synthase activity and their nucleotides are incorporated into DNA. However, it is evident that several differences occur in the underlying antitumor mechanisms associated with these nucleoside analogues. Recently, TAS-102 (composed of FTD and tipiracil hydrochloride, TPI) was shown to prolong the survival of patients with colorectal cancer who received a median of 2 prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 28 publications
3
44
0
Order By: Relevance
“…Why does loss of TK1 confer FTD resistance? Similar to thymidine, once FTD is transported into the cytoplasm of tumor cells by nucleoside transporters, hENT1, hENT2 (5,6), or hCNT1 (21), it is activated by sequential phosphorylation by TK, TYMK, and NDK. FTD cytotoxicity is possibly mediated by the inhibition of TS activity by FTD-MP (10) and the incorporation of FTD-TP into DNA (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why does loss of TK1 confer FTD resistance? Similar to thymidine, once FTD is transported into the cytoplasm of tumor cells by nucleoside transporters, hENT1, hENT2 (5,6), or hCNT1 (21), it is activated by sequential phosphorylation by TK, TYMK, and NDK. FTD cytotoxicity is possibly mediated by the inhibition of TS activity by FTD-MP (10) and the incorporation of FTD-TP into DNA (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Trifluridine (FTD) is a fluorinated nucleoside analogue and a cytotoxic component of TFTD, and tipiracil hydrochloride is a thymidine phosphorylase (TP) inhibitor that suppresses the degradation of FTD in vivo and maintains the FTD concentration in the bloodstream (3). Once FTD is transported into the cytoplasm of tumor cells by nucleoside transporters, such as equilibrative nucleoside transporter 1 (hENT1) or hENT2 (4)(5)(6), it is phosphorylated to monophosphate (FTD-MP), diphosphate, and triphosphate (FTD-TP) forms by thymidine kinase (TK), thymidylate kinase (TYMK), and nucleoside diphosphate kinase (NDK), respectively, exerting cytotoxic effects via incorporation into DNA (7)(8)(9). In addition, FTD-MP inhibits thymidylate synthase (TS; refs.…”
Section: Introductionmentioning
confidence: 99%
“…TAS‐102 is an oral antitumor drug that contains the thymidine‐based nucleic acid analog trifluridine (FTD) and the thymidine phosphorylase inhibitor tipiracil hydrochloride (TPI) at a molar ratio of 1:0.5. FTD becomes incorporated into DNA and causes DNA dysfunction and damage . Although FTD is rapidly degraded to its inactive form in the intestines and liver, TPI assists in maintaining the blood concentration of FTD by inhibiting thymidine phosphorylase .…”
Section: Introductionmentioning
confidence: 99%
“…An immunohistochemical study indicated that ENT1 and ENT2 are predominantly expressed in the lateral membrane of human enterocytes (Govindarajan et al, ). In addition, the uptake of FTD by a colorectal cancer cell line was inhibited by the ENT inhibitors, S‐(4‐nitrobenzyl)‐6‐thioinosine (NBMPR) and dipyridamole (Kitao et al, ; Sakamoto et al, ). Moreover, the systemic exposure of FTD was shown to increase linearly in patients with advanced solid tumor (Doi et al, ).…”
Section: Introductionmentioning
confidence: 99%